2019
DOI: 10.1016/j.psychres.2018.12.155
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and impulsivity: The relationship of psychopathy to different aspects of UPPS-P impulsivity

Abstract: Impulsivity is thought to be a major component of psychopathy. However, impulsivity is a multi-faceted concept, and different facets may have differential relationships to psychopathy. We measured impulsivity via the UPPS-P in a sample of prisoners and in patients in a personality disorder service resident in secure psychiatric care. Psychopathy in the prison sample was measured via the clinician-rated Psychopathy Checklist: Screening Version and in the patients via the Psychopathy Checklist-Revised. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 62 publications
(80 reference statements)
9
29
0
2
Order By: Relevance
“…The results show that sensation seeking is positively related to boldness, meanness and disinhibition in the community sample, whereas in the forensic patients sample it is only positively related to meanness and disinhibition. These results are somewhat consistent with earlier findings in a community sample (Dickey, 2014) and also consistent with the findings of Weidacker et al (2017) where the TriPM (Patrick et al, 2009) was also usedbut differ from those of Gray et al (2019), who did not find a relationship between sensation seeking and psychopathy in forensic patients. From these results it can be concluded that sensation seeking is related to callous-unemotional and disinhibitory tendencies in both the community and the forensic population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results show that sensation seeking is positively related to boldness, meanness and disinhibition in the community sample, whereas in the forensic patients sample it is only positively related to meanness and disinhibition. These results are somewhat consistent with earlier findings in a community sample (Dickey, 2014) and also consistent with the findings of Weidacker et al (2017) where the TriPM (Patrick et al, 2009) was also usedbut differ from those of Gray et al (2019), who did not find a relationship between sensation seeking and psychopathy in forensic patients. From these results it can be concluded that sensation seeking is related to callous-unemotional and disinhibitory tendencies in both the community and the forensic population.…”
Section: Discussionsupporting
confidence: 92%
“…This relationship was also found by Weidacker et al (2017) in both a forensic and a non-forensic sample using the sensation seeking subscale of the UPPS-P Impulsive Behaviour Scale (Lynam et al, 2006). However, the same group (Gray et al, 2019) failed to find an association between sensation seeking and psychopathic traits using the Psychopathy Checklist -Revised (PCL-R; Hare, 1991) and the Psychopathy Checklist: Screening Version (PCL:SV; Hart et al, 1995).…”
Section: Sensation Seeking Psychopathic Traits Impulsivity and Aggressionmentioning
confidence: 99%
“…Both networks saw the UPPS-P nodes emerge as well-connected components of psychopathy regardless of measurement modality (i.e., in both the PCL:SV and LSRP networks). This finding is consistent with literature evincing relatively consistent links among the variables measured by the UPPS-P and psychopathy across measures (e.g., Gray et al, 2019). We also found divergent associations among Factor 1 and Factor 2 psychopathy items in relation to negative and positive urgency.…”
Section: Consistencies Across Measuressupporting
confidence: 92%
“…The narcissistic and psychopathic schemata may also lead to difficulties in regulating negative affect and to disinhibition in behavior (Gray, Weidacker & Snowden, 2019). For example, it has been reported that offenders with high levels of psychopathy exhibited a higher cardiovascular response when they processed negative, rather than positive information, in comparison to those with low levels of psychopathy (Casey, Rogers, Burns & Yiend, 2017).…”
Section: Organization Of Responses (Affect and Behavior Domains)mentioning
confidence: 99%